The role of intraoperative positioning of the inferior alveolar nerve on postoperative paresthesia after bilateral sagittal split osteotomy of the mandible: prospective clinical study - Hanzelka, T; Foltán, R; Pavlíková, G; Horká, E; Sedý, J (International journal of oral and maxillofacial surgery, 2011)
Bilateral sagittal split osteotomy (BSSO) aims to correct congenital or acquired mandibular abnormities. Temporary or permanent neurosensory disturbance is the most frequent complication of BSSO. To evaluate the influence of IAN handling during osteotomy, the authors undertook a prospective study in 290 patients who underwent BSSO. The occurrence and duration of paresthesia was evaluated 4 weeks, 3 months, 6 months, and 1 year after surgery. Paresthesia developed immediately after surgery in almost half of the patients. Most cases of paresthesia resolved within 1 year after surgery. A significantly higher prevalence of paresthesia was observed on the left side. The authors found a correlation between the type of IAN position between the left and right side. The type of split (and IAN exposure) did not have a significant effect on the occurrence or duration of neurosensory disturbance of the IAN. The authors did not find a correlation between the occurrence and duration of paresthesia and the direction of BSSO. Mandibular hypoplasia or mandibular progenia did not represent a predisposition for the development of paresthesia. In the development of IAN paresthesia, the type of IAN exposure and the split is less important than the side on which the split is carried out.
Keywords: následné studie; Female; lidé středního věku; techniky fixace čelistí; Follow-Up Studies; malokluze; Adolescent; mužské pohlaví; mladý dospělý; prospektivní studie; parestezie; Humans; dospělí; Paresthesia; Prospective Studies; Mandibular Nerve; poranění trojklaného nervu; Statistics, Nonparametric; nervus mandibularis; Postoperative Complications; lidé; sagitální osteotomie větve dolní čelisti; Middle Aged; Mandible; Malocclusion; mandibula; ženské pohlaví; Treatment Outcome; Jaw Fixation Techniques; neparametrická statistika; pooperační komplikace; Osteotomy, Sagittal Split Ramus; Young Adult; Adult; Trigeminal Nerve Injuries; Male; mladiství; výsledek terapie